he Analysis of the Effect of Systemic Lupus Erythematosus Selected Indicators and Its Treatment on Bone Mineral Density - Tsyhanyk L.; Abrahamovych U.; Romaniuk O. (Львівський клінічний вісник, 2018)
Introduction. The lesions of the bone and joint system start to appear during the first ten years of disease in 25.0 % of patients with SLE. The prevalence of osteopenia ranges from 4.0 to 74.0 % and the prevalence of osteoporosis – from 3.0 to 48.0 %. The main reasons for such disappointing statistics are chronic autoimmune inflammation and prolonged treatment with glucocorticoids (GCs), which coupled with traditional osteoporosis triggers like age, smoking, changes in hormone levels, lead to the rapid loss of bone mass. However, the issue of osteoporosis and factors affecting the condition of bone tissue in patients with SLE has not been studied sufficiently. The aim of study. The objective is to analyze the effect of SLE selected indicators and its treatment on bone mineral density. Materials and methods. The study involved 123 women aged 21 to 51 years (average age at the time of the survey – 40.37 ± 0.95). The average duration of the disease was 7.35 ± 0.27. The average total amount of exacerbations (in years) was 9.97 ± 0.60, the average total duration of exacerbations (in days) was 148.80 ± 10.24. 100.0 % of patients received methylprednisolone at the daily dose of (based on prednisolone) 5.0 – 30.0 mg (average daily dose was 11.04 ± 0.46 mg, average total dose was 31.40 ± 1.92 g). The average duration of GC treatment was consistent with the average duration of the disease. The control group included 25 practically healthy premenopausal women of the corresponding age. To achieve the stated objective, the first step was to determine bone mineral density by means of dual energy X-ray absorptiometry in treatment and control groups and compare the obtained results. The second step was to study the relationship between bone mineral density and the disease activity according to the SLE Disease Activity Index (SLEDAI) score. Patients with SLE were divided into groups according to their T-scores (a group with unaffected bone mineral density, a group with osteopenia and osteoporosis) and according to the SLEDAI scores (groups: no activity, mild activity, moderate activity, high activity, very high activity). The third step was to determine the relationships between bone mineral density scores and the SLICC / ACR Damage Index scores, the duration of the disease, the number and duration of exacerbations, the average and total doses of glucocorticoids. Results. According to the results of lumbar spine DXA scans among the women of the treatment group, 75.7 % of them had decreased bone mineral density. However, only 32.0 % of women in the control group had decreased bone mineral density (p < 0.001). According to the results of proximal femur DXA scans among the women of the treatment group, 35.5 % of them had decreased bone mineral density. However, only 16.0 % of women in the control group had decreased bone mineral density (p < 0.05) The average T-scores obtained due to lumbar spine DXA scans in both groups were significantly different and were lower in patients with SLE. The average T-scores obtained due to proximal femur DXA scans in both groups did not have a significant difference. According to percentile distribution, T-scores in treatment group was in the range (-2.02) – (-1.21), in control group (-1,08) -1,08); the medians were -0.1 and (-0.3) respectively. According to the results of our study, there is no statistical validity of the difference between groups divided by T-scores, which suggests that there is no relationship between the activity of SLE and the state of bone mineral density. The analysis of the correlation between bone mineral density scores and SLICC/ACR Damage Index scores reveals that there is a reliable association ((r = (- 3.40), p < 0.001). An inverse relationship was found between bone mineral density and the duration of disease ((r = (-0.36), p <0.01), the total number of exacerbations ((r = (- 0.49), p < 0.001) and the total duration of exacerbations ((r = (- 0.56), p < 0.001). Similar associations were also revealed by the results of analysis of relationship between bone mineral density and GC treatment, which was measured by the average dose ((r = (- 0.59), p < 0.001) and the total dose ((r = (- 0.52), p < 0.001). Conclusions. The analysis of the effect of SLE selected indicators and its treatment on bone mineral density revealed that: 1) the percentage of women with decreased bone mineral density was significantly higher in the treatment group than in the control group (lumbar spine DXA scans – 75.7 % (35.5 %), proximal femur DXA scans – 35.5 % (16.0 %), respectively), and the average T-scores for lumbar spine scans were significantly lower in patients with SLE than in the control group – (-1.41) ± 1.15 and (-0.55) ± 0.99, respectively. 2) there is no reliable correlation between bone mineral density and the disease activity according to SLEDAI; 3) there is a inverse relationship between the bone mineral density and SLICC / ACR Damage Index, the duration of disease, the total number and duration of SLE exacerbations, as well as the total dose of glucocorticoids.